PENGARUH CAR, NPF, DAN GIRO WAJIB MINIMUM TERHADAP PROFITABILITAS DENGAN FDR SEBAGAI VARIABEL INTERVENING - Aviana, Herlanda; Pratama, Abdul Aziz Nugraha (Institut Agama Islam Negeri (IAIN) Ternate, 2023)
The background of this research because operational costs of Islamic banks are higher than those of conventional banks, where both of them compete with each other to get the desired profit. This study aims to determine the effect of CAR, NPF, and GWM on Return On Assets (ROA) with the Financing to Deposit Ratio (FDR) as an Intervening Variable in Islamic Commercial Banks in Indonesia. This research uses quantitative research methods. Samples were taken from 10 Islamic banks registered with OJK for the period 2017 – 2021. This research uses secondary data, using the Purposive Sampling method. The software used is E-Views 9 using linear regression analysis. The results of the t test show that the Capital Adequacy Ratio variable has a positive effect on profitability. Non-performing financing variables have a positive effect on profitability. The Minimum Statutory Reserves variable has a positive effect on Profitability. Based on the Path Analysis test, FDR was unable to mediate the effect of CAR on ROA. FDR is able to mediate the effect of NPF on ROA. FDR is able to mediate the effect of GWM on ROA.Keywords: CAR; NPF; GWM; ROA; FDR